2022
DOI: 10.1073/pnas.2123424119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation and hippocampal ripple disruption after one-session learning eliminate memory expression the next day

Abstract: Memory reactivation during non–rapid-eye-movement ripples is thought to communicate new information to a systems-wide network and thus can be a key player mediating the positive effect of sleep on memory consolidation. Causal experiments disrupting ripples have only been performed in multiday training paradigms, which decrease but do not eliminate memory performance, and no comparison with sleep deprivation has been made. To enable such investigations, we developed a one-session learning paradigm in a Plusmaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…In contrast, in Overlapping the fraction of long-ripples following a delta-wave increased while the fraction of ripples occurring during a spindle after a delta wave (D-SwR) decreased. We had already previously observed that the increase of delta and spindles and their coupling was linked to simple experiences [14], and this coupling is most often reported by researchers investigating human subjects with simple, associative memory paradigms such as paired-associative word-list or reinforced spatial learning [47,61]. This fits to our current results, where delta-spindle coupling increased after our simple memory condition (Stable).…”
Section: Oscillation-coupling For Memory Consolidationsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, in Overlapping the fraction of long-ripples following a delta-wave increased while the fraction of ripples occurring during a spindle after a delta wave (D-SwR) decreased. We had already previously observed that the increase of delta and spindles and their coupling was linked to simple experiences [14], and this coupling is most often reported by researchers investigating human subjects with simple, associative memory paradigms such as paired-associative word-list or reinforced spatial learning [47,61]. This fits to our current results, where delta-spindle coupling increased after our simple memory condition (Stable).…”
Section: Oscillation-coupling For Memory Consolidationsupporting
confidence: 91%
“…NonRapid-Eye-Movement (NonREM) sleep has been proposed as a critical stage in offline memory processing [11,12]. The reactivation of cells active during encoding, also referred to as neural reactivation, has been shown to occur during quiet wake and NonREM sleep and is potentially crucial to memory consolidation [13][14][15][16]. These reactivation events occur during hippocampal high frequency burst oscillations (100-250 Hz) referred to as ripples [17].…”
Section: Introductionmentioning
confidence: 99%
“…Aleman-Zapata et al. ( 32 ) explored the connection between hippocampal ripples and high-frequency oscillations in the cortex during sleep-dependent consolidation after one-trial spatial learning in rats. With this hippocampal ripple–dependent task, they report cortical oscillations of two high frequencies, with each high frequency involving a distinct neural network—a prefrontal–parietal network for faster oscillations and a hippocampal–parietal network for slower oscillations.…”
Section: Mechanisms Underlying the Sleep–memory Connectionmentioning
confidence: 99%
“…This often leads to studies overtraining animals on simple tasks (e.g., track running), and to limited recording time (1-2 h) after training. Depending on time of day and habituation, an animal will sleep 30-60% of those initial hours after training [26] -mainly remaining in NREM sleep, which often prevents analyzing potential REM reactivations.…”
Section: Box 3 Investigating Memory Reactivation In Rodentsmethodolog...mentioning
confidence: 99%
“…Memory reactivations have been closely tied to sharp wave-ripple (SWRs) activity arising from the hippocampus [19] but have also been recorded across a wide range of brain regions (e.g., [20,21]). A direct role of memory reactivations in memory consolidation is suggested by their association with improved post-sleep performance (e.g., [22,23]) and by the fact that their suppression (e.g., by disrupting SWRs after learning) impairs memory performance (e.g., [24][25][26]).…”
Section: Memory Reactivations: Pioneering Work In Rodentsmentioning
confidence: 99%